2020
DOI: 10.1101/2020.02.10.942300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rpgrip1l controls ciliary gating by ensuring the proper amount of Cep290 at the vertebrate transition zone

Abstract: A range of severe human diseases called ciliopathies are caused by the dysfunction of primary cilia. Primary cilia are cytoplasmic protrusions consisting of the basal body (BB), the axoneme and the transition zone (TZ). The BB is a modified mother centriole from which the axoneme, the microtubule-based ciliary scaffold, is formed. At the proximal end of the axoneme, the TZ functions as the ciliary gate governing ciliary protein entry and exit. Since ciliopathies often develop due to mutations in genes encoding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Regarding the impact of ANKS3 on the composition of TZ, the fact that the amount of NPHP1 is decreased under both mutant and KD_ANKS3 conditions is consistent with the downregulation of the Nphp1 transcript in mIMCD3 cells. Notably, the level of NPHP4 at TZ was not affected, which is expected because recruitment of NPHP4 to TZ does not require NPHP1 as shown in several cell types (38). In contrast, TMEM67 was absent from TZ in KD_ANKS3 cells while unchanged in P269L mutant cells.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding the impact of ANKS3 on the composition of TZ, the fact that the amount of NPHP1 is decreased under both mutant and KD_ANKS3 conditions is consistent with the downregulation of the Nphp1 transcript in mIMCD3 cells. Notably, the level of NPHP4 at TZ was not affected, which is expected because recruitment of NPHP4 to TZ does not require NPHP1 as shown in several cell types (38). In contrast, TMEM67 was absent from TZ in KD_ANKS3 cells while unchanged in P269L mutant cells.…”
Section: Discussionmentioning
confidence: 63%
“…One study screened a library of 273 kinase inhibitors and identified thiazovivin (a pyrimidine-based non-selective ROCK inhibitor) as a significant hit (63). It is also interesting to note that the plant flavanoid, eupatilin, which was highlighted as a potential therapeutic for CEP290 -related retinal dystrophy (11) and has been used to treat the Rpgrip1l -/- mouse (64), has an indirect effect on actin cytoskeleton remodelling that is mediated by CEP290 (65). Several other screens have identified other biological targets for the restoration of cilia, for example a screen to identify drugs that restore cilia expression in cancer cells identified 118 compounds, many of which affect levels of cAMP, calcium or other ions (66).…”
Section: Discussionmentioning
confidence: 99%
“…Eupatilin, a compound able to rescue ciliogenesis in CEP290 invalidated cells (see below), directly modulates the calmodulin/NPHP5 interaction therefore increasing the amount of NPHP5 at the transition zone in the absence of CEP90 ( Kim et al, 2018 ). Interestingly, Eupatilin was recently shown to improve cilia-related phenotypes in the context of RPGRIP1L/NPHP8 suggesting that it might present broader potential in transition zone-related NPH ( Wiegering et al, 2021 ).…”
Section: Pharmacotherapymentioning
confidence: 99%